From larva to adult: In vitro rearing protocol for honey bee (Apis mellifera) drones. - Marina Carla Bezerra da Silva; Madison Gail Kindopp; Midhun Sebastian Jose; Oleksii Obshta; Thanuri Lakna Kumari Edirithilake; Emilio Enrique Tellarini Prieto; Muhammad Fahim Raza; Marcelo Polizel Camilli; Jenna Thebeau; Fatima Masood; Ivanna Kozii; Igor Moshynskyy; et al. (PLoS ONE)
Development of a successful in vitro rearing protocol has been essential for pesticide safety assessment of immature honey bee workers under laboratory conditions. In contrast, pesticide safety testing of honey bee drones is limited, in part due to the lack of successful laboratory rearing protocols for this reproductive caste. Considering that healthy drones are essential for successful mating and reproduction of the honey bee queen, a standardized in vitro rearing protocol for honey bee drones is necessary to support reproductive safety studies, as well as to gain a deeper understanding of honey bee drone development. Using the established in vitro rearing protocol for honey bee workers, we modified the days of grafting and pupal transfer, as well as the diet volume, pupation plate orientation, and absorbent tissue in the pupal wells to successfully rear honey bee drones in vitro. In vitro-reared drones were evaluated for gross wing abnormalities, body weight, testes weight, and abdominal area, and compared with age-matched drones reared in field colonies. We found that honey bee drones reared in a vertically oriented pupation plate containing WypAll® absorbent tissue in each well had a mean survival to adulthood of 74 ± 3.5% (SEM) until adulthood. In contrast, drones reared in a horizontally oriented pupation plate containing Kimwipe® absorbent tissue in each well had significantly lower survival (5.5 ± 2.3%) and demonstrated gross wing abnormalities. All in vitro-reared drones had significantly lower body weight, testes weight and abdominal area relative to colony-reared control drones. Accordingly, we successfully developed an in vitro rearing protocol for honey bee drones which has the potential to improve future reproductive safety assessment of pesticides for honey bees.